(untitled) (Research, Society and Development, 2022)
There are many ways to diversify food in a healthy and sustainable way, and Unconventional Food Plants (PANC) have been widely used. The aim of the study was to assess the knowledge and use of PANC by university students. Qualiquantitative and transversal research was carried out with university students from Campus Rio Paranaíba, Federal University of Viçosa, through an online questionnaire, to evaluate 10 PANC, whose data are presented by descriptive statistics. Most university students reported that they had already obtained information about PANC, and 41% did not use to consume it, and 57% did not find it in supermarkets, markets or fairs. Most did not describe the name of some PANC (purslane, ora-pro-nóbis and serralha), with peixinho being the most recognized plant due to the correct description of its name. The highest weekly intake was of water squash and jurubeba, and the rarest was of goya and gizzard. Some university students were unaware of the PANC studied, since they cited incorrect names or did not mention them, and most did not use and did not know about their nutrients or prominent active compounds. It is concluded that actions are needed to expand the knowledge and use of PANC, aiming at a diversified, sustainable, safe and nutritious diet, which can contribute to family farming and the sustainability of the planet.